Influence of a competition model on the market behavior of a cargo motor transport enterprise - E. V. Tabachnikova (Вестник СибАДИ, 2017)
The article dwells upon the peculiarities of influencing a competition model in a sector on an enterprise’s market behavior. There is implemented an analysis of the competition model that characterizes the trucking market. There are presented sectoral peculiarities of the market behavior of transport companies. There are identified the main ways of obtaining economic benefit by a cargo motor transport enterprise.